Faktor-faktor resiko kejadian pneumonia pada pasien pneumonia usia 12-59 bulan di RSUD Wangaya - Susan Natalia Budihardjo; I Wayan Bikin Suryawan (DiscoverSys Inc., 2020)
Background:Â Pneumonia is the leading cause of under five childrenâ€™s mortality worldwide. In Indonesia, pneumonia still the second largest cause of mortality in infants (12.3%) and under five children (13.2%) after diarrhea. However, the incidence of pneumonia didnâ€™t receive some attention so itâ€™s often referred as â€œthe forgotten killer of childrenâ€. Therefore, the aim of our study is to control pneumonia in children under five by investigating the risk factors of pneumonia.Methods:Â A case control study was conducted from January 2019 to May 2019 by using the consecutive sampling methods. The subjects were children aged 12-59 months old with pneumonia at Wangaya Hospital for the case and children aged 12-59 months old without pneumonia at Wangaya Hospital for the control. Subjectâ€™s characteristics such as gender, age, weight birth, immunization status, exclusive breastfeeding status, history of asthma, smoke exposure, and nutritional status. Matching was performed on exclusive breastfeeding variable. Will be done the bivariate analysis with McNemar and multivariate analysis with logistic regression.Result:Â Among 96 subjects divided into 48 subjects in each group. Bivariate analysis showed that immunization status (p-value 0.009, OR 5.209) and smoke exposure (p-value 0.008, OR 2.238) were the significant risk factors of pneumonia. While gender, nutritional status, and history of asthma werenâ€™t significant risk factors of pneumonia in children under five at Wangaya Hospital.Conclusion:Â Incomplete immunization status and exposed to cigarette smoke are the risk factors of pneumonia in children aged 12-59 months old at Wangaya Hospital.Â Latar Belakang:Â Pneumonia merupakan pembunuh nomor satu balita di dunia. Di Indonesia, Pneumonia menduduki peringkat kedua penyebab kematian bayi (12,3%) dan balita (13,2%) setelah diare. Sayangnya, kejadian pneumonia tidak begitu banyak mendapat perhatian khusus. Tujuan penulisan laporan kasus ini adalah mempelajari faktor-faktor resiko yang menyebabkan pneumonia.Metode:Â Dengan menggunakan studi kasus-kontrol yang dilakukan pada bulan Januari 2019-Mei 2019 menggunakan metode sampel konsekutif. Subjek penelitian adalah anak berusia 12-59 bulan dengan pneumonia di RSUD Wangaya untuk kasus, dan anak berusia 12-59 bulan tidak dengan pneumonia di RSUD Wangaya untuk kontrol. Karakteristik subjek berupa jenis kelamin, usia, berat badan lahir, status ASI eksklusif, status imunisasi, riwayat asma, paparan asap, dan status gizi. Dilakukan matching pada variabel ASI eksklusif. Dan akan dilakukan analisis bivariat dengan uji McNemar dan multivariat dengan regresi logistik.Hasil: Sebanyak total 96 subjek, dengan 48 subjek untuk masing-masing kelompok penelitian. Didapatkan hasil yang signifikan pada faktor resiko status imunisasi (nilai p 0.009 dan OR 5.209) dan faktor resiko paparan asap (nilai p 0.008 dan OR 2.238). Sedangkan jenis kelamin, status gizi, dan riwayat asma tidak didapatkan hasil yang signifikan sebagai fakto resiko pneumonia di RSUD Wangaya.Simpulan: Status imunisasi yang tidak lengkap dan terpapar asap rokok merupakan faktor resiko terjadinya pneumonia pada anak usia 12-59 bulan di RSUD Wangaya.